Migration and terrorism - Tim Krieger (Albert-Ludwigs-Universität Freiburg, Wilfried-Guth-Stiftungsprofessur für Ordnungs- und Wettbewerbspolitik, 2020)
This chapter explores the complex interaction between migration and terrorism. It proposes a 'terrorism-migration cycle' to investigate systematically this interaction at every stage of the migration process. Importantly, no stage of the migration process is independent of what happened on the previous stage, affecting how terrorism and migration interact. It is shown that terrorism may be a trigger of migration in the origin country, that only particular selections of migrants choose to leave a country, and that these migrants then sort into different destinations. The role of migration governance as a means to avoid the influx of potential terrorists is explored as well as the responses of destination-country populations and governments to the threat of imported terrorism. As yet other challenges, homegrown terrorism within immigrant communities and political violence directed against immigrants are discussed. Finally, it is argued that there are feedback effects of diasporas on the origin countries of immigrant communities.
Keywords: 330; Terrorismus; Internationale Migration; Migrationspolitik; Theorie